Effect of cooking methods on vitamin C, vitamin E, and carotenoids in selected vegetables - Brahma Achariyalage, Dilini (My University, 2025)
Vegetables are rich sources of vitamins, such as vitamin C and vitamin E, and pigments such as carotenoids, which serve as vitamin precursors. Since humans are unable to synthesize these essential micronutrients, they need to be obtained through diet in adequate amounts. In addition to nutritional value, these compounds exhibit antioxidant activity. They are often susceptible to degradation during food processing. Ready-made meals are widely consumed and often contain vegetables subjected to heat treatments such as steam oven and microwave reheating at home. However, the effects of these processes on nutrients are underexplored. This study aimed to evaluate the impact of different cooking methods –microwave, steam oven, and steam oven + microwave – on the vitamin C, vitamin E, and carotenoid content of commonly consumed vegetables, namely kale (Brassica oleracea L. var. acephala), bell pepper (Capsicum annuum L.), tomato (Solanum lycopersicum L.), and carrot (Daucus carota L.). The steam oven treatment involved a longer duration of heat exposure, while the microwave treatment was shorter. The quantitative analysis of vitamins involved Ultra-High-Performance Liquid Chromatography (UHPLC) with a diode array detector (DAD) for vitamin C, which was analysed as ascorbic acid, UHPLC with a fluorescence detector (FLD) for vitamin E, which was analysed as tocopherols, and spectrophotometric analysis for total carotenoid quantification. Fresh vegetables contained higher concentrations of all analyzed vitamins and carotenoids compared to the heat-treated ones. Microwave heating preserved the most nutrients, where only 5%–19% reduction for ascorbic acid, 14% reduction for α-tocopherol in kale, and 0%–48% reduction for carotenoids compared to the fresh counterparts were observed. Conversely, steam oven + microwave treatment showed a greater loss of all nutrients, with a reduction of 78%–96% for ascorbic acid, 31% for α-tocopherol in kale, and 22%–76% for carotenoids. A similar effect was observed for steam oven treatment. Notably, α-tocopherol in bell peppers remained stable across all heat treatments. The extent of the impact on nutrients also varied depending on the type of vegetable. These results suggest that vegetables consumed fresh contain the highest nutritional value, whereas microwave cooking preserves more nutrients than steam oven treatments.
Keywords: vitamin C, vitamin E, carotenoid, vegetable, cooking, heat treatment